Analysis of a Kanban Discipline for Cell Coordination in Production Lines. I - Mitra, Debasis; Mitrani, Isi (Management Science, 1990)
We describe and analyze a discipline called kanban for the coordination of cells in a large-scale manufacturing facility. There are many cells in a tandem configuration and a fixed number of cards (or kanbans in Japanese usage) in each cell. The cards circulate within the cell and their presence at designated positions signals to the neighboring cells the status of the cell's inventory; rules specify the timing of the movement of parts from cell to cell. We construct a stochastic model of the whole manufacturing facility and give our results in three parts. First, the kanban discipline is compared to the classical production discipline and it is shown to dominate the classical discipline in terms of throughput. Secondly, we give a scheme for analyzing approximately the performance of the kanban system by examining first a single cell in isolation and then combining the isolated cells through fixed-point equations. Thirdly, we report on extensive experiments and on their numerical results which are obtained from simulations and our method of analysis. The throughput-inventory relationship of the kanban scheme is observed to be superior to that of the classical discipline.